FACTORS ASSOCIATED WITH BURNOUT AMONG NURSES DURING COVID-19 PANDEMIC: A SCOPING REVIEW - Wati, Suis Galischa; Sutrimo, Ade (Jurnal Keperawatan Respati Yogyakarta, 2022)
The current COVID-19 pandemic has become a serious threat and difficult challenge for global health. This detrimental condition increases nurses' workload, the risk of fatigue and can cause stress on nurses that can induce burnout. Untreated burnout must be examined thoroughly because it can lead to a decrease of nurses’ performance and prompted to nursing errors that will affect the quality of health services and patient care outcomes. However study related to nursing burnout is still rarely performed. This scoping review aimed to identify several factors related to burnout in nurses during the COVID-19 pandemic. This study was conducted between January-March 2021 by searching and analyzing all eligible studies from several electronic databases including ProQuest, Science Direct, Scopus, and Springer Link for related articles published from 2019 to 2021. The following terms were used in the search: burnout, nursing burnout, cause of nursing burnout, and COVID-19. A systematic process using The Preferred Reporting Items for Systematic Reviews and a Meta-Analyses (PRISMA) guideline were carried out in the review process. A total of 10 article journals were finally selected of 343 studies. Sociodemographic factors (female, marriage, having child, education qualification, age, and ethnicity), psychological factors (depression, stress, anxiety, resilience, and self-efficacy), and also occupational factors (workload, job demands, working environment, working as a front line worker, direct contact with a COVID-19 patient, availability of personal protective equipment, and salary) were identified as factors that influenced burnout syndrome among nurses during the COVID-19 pandemic. Keywords: Nurse; Burnout; Covid-19; Pandemic; Nursing Manager